1997
DOI: 10.1093/clinchem/43.6.1072
|View full text |Cite
|
Sign up to set email alerts
|

Platelet distribution width for differential diagnosis of thrombocytosis

Abstract: Differential diagnosis of thrombocytosis is not always obvious. The routine clinical chemistry laboratory classically provides only limited help in distinguishing between reactive thrombocytosis (RT) and autonomous thrombocytosis, where platelet production escapes normal regulatory processes, and which is seen in myeloproliferative diseases (MPD) such as essential thrombocythemia and polycythemia vera. We explored the clinical use of platelet distribution width (PDW) in the differential diagnosis of thrombocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 10 publications
4
55
0
5
Order By: Relevance
“…Studies have also shown that PDW was useful in the differential diagnosis of thrombocytosis and thrombocytopenia. 23,24 Our results further support the measurements of MPV and PDW would be useful for independent predictors of diabetes macrovascular complications, which need more studies to confirm. Diabetic neuropathy is one of the most serious complications of diabetes, with an estimated prevalence of 13.1% in patients with known diabetes and 7.1% in newly diagnosed diabetic patients.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have also shown that PDW was useful in the differential diagnosis of thrombocytosis and thrombocytopenia. 23,24 Our results further support the measurements of MPV and PDW would be useful for independent predictors of diabetes macrovascular complications, which need more studies to confirm. Diabetic neuropathy is one of the most serious complications of diabetes, with an estimated prevalence of 13.1% in patients with known diabetes and 7.1% in newly diagnosed diabetic patients.…”
Section: Discussionsupporting
confidence: 70%
“…However, the instrument has not been validated for LFR, MFR, HFR, IRF, MPV, P‐LCR, PCT, and PDW; thus, these data may be useful in future studies. However, the clinical value of these new indices has been investigated in only a few studies in human 19–21 and veterinary hematology 22,23 . Within‐laboratory precision of the analyzer with human control samples and repeatability with canine blood were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…However only nine patients presenting with CARS scored falling in the severe range participated in this study and studies with higher sample sizes of severe autism are needed to explicate this point. PDW is an indication of variation in volume of platelets and increases in the presence of platelet anisocytosis [Osselaer, Jamart, & Scheiff, 1997]. PDW is a test obtained from direct flow cytometric measurement of platelet cell volume and is not well documented at the clinical setting (Dixon, 1997;van der Loo & Martin, 1997).…”
Section: Discussionmentioning
confidence: 99%